An Experimental Examination of Demand-Side Preferences for Female and Male National Leaders - Murray, Gregg R.; Carroll, Bruce A. (Frontiers in Psychology, 2020)
Females constitute a far smaller proportion of political leaders than their proportion in the general population. Leading demand- and supply-side explanations for this phenomenon account for some of the variance but leave a great deal unexplained. This research evaluates the issue using the biological theory of evolution by natural selection. It experimentally assesses how varying types of inter- and intragroup threat—a recurring ancestral problem—affect demand for female and male national leaders. This work analyzes data collected from individuals (N = 826) in the U.S. during the 2012 Cooperative Congressional Election Study. The results suggest the predominant preference for male over female leaders in some contexts may be the non-adaptive and non-functional but lingering outcome of an adaptive preference for physically formidable allies that was shaped by natural selection in ancestral environments.